The influence of water activity on thermal stability of horseradish peroxidase - Hendrickx, M. (2011)
The thermal stability of horseradish peroxidase in the solid state was studied as a function of water activity, from 0.11 to 0.88. At all activities the enzyme was found to be much more stable in the solid state than in solution. Inactivation temperatures were in the range of 140–160°C. Inactivation curves show a biphasic behaviour which can be described by a model assuming two fractions (heat labile and heat stable) with independent first order inactivation kinetics. The labile fraction represents approximately 30% of the total activity. The z-value for both stable and labile fractions depends on water activity (moisture content) and has a maximum at aw= 0.76 (44.4°C and 43.8°C, respectively).